Strain and temperature characteristics of the LP11 mode based on a few-mode fiber Bragg grating and core-offset splicing. (17th January 2018) - Jin, Wenxing; Xu, Yao; Jiang, Youchao; Wu, Yue; Yao, Shuzhi; Xiao, Shiying; Qi, Yanhui; Ren, Wenhua; Jian, Shuisheng
Abstract: We propose and demonstrate a ring fiber laser based on a few-mode fiber Bragg grating for strain and temperature sensing using only the L P 11 mode. The core-offset splicing method is used to ensure effective coupling from the fundamental mode to the L P 11 mode. A stable erbium-doped fiber laser operating as a single L P 11 mode with a 3 dB linewidth of about 0.02 nm and an optical signal-to-noise ratio over 42 dB is achieved by appropriately adjusting the polarization controller between the optical circulator and the few-mode fiber Bragg grating. A high axial strain sensitivity of 0.8778 pm μ ε − 1 and a temperature sensitivity of 9.9214 pm ° C − 1 are achieved with the advantages of all-fiber, simple construction and easy control.